2009
DOI: 10.1016/j.ymgme.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Processing of alkylcobalamins in mammalian cells: A role for the MMACHC (cblC) gene product

Abstract: The MMACHC gene product of the cblC complementation group, referred to as the cblC protein, catalyzes the in vitro and in vivo decyanation of cyanocobalamin (vitamin B 12 ). We hypothesized that the cblC protein would also catalyze the dealkylation of newly internalized methylcobalamin (MeCbl) and 5′-deoxyadenosylcobalamin (AdoCbl), the naturally occurring alkylcobalamins that are present in the diet. The hypothesis was tested in cultured endothelial cells using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 26 publications
6
109
0
4
Order By: Relevance
“…Demethylation of MeCbl was much faster than the removal of the 5 ′ -adenosyl group from AdoCbl (11.7 ± 0.2 and 0.150 ± 0.006/h, respectively) [ 38 ]. In addition, MMACHC was capable of dealkylating a series of MeCbl analogues namely, ethylcobalamin, propylcobalamin, butylcobalamin, pentylcobalamin and hexylcobalamin [ 37 ]. MMACHC catalyzed the removal of the alkyl group at the upper axial position of all of the MeCbl analogs, however, the rate of dealkylation decreased with increasing alkyl chain length [ 38 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 98%
See 2 more Smart Citations
“…Demethylation of MeCbl was much faster than the removal of the 5 ′ -adenosyl group from AdoCbl (11.7 ± 0.2 and 0.150 ± 0.006/h, respectively) [ 38 ]. In addition, MMACHC was capable of dealkylating a series of MeCbl analogues namely, ethylcobalamin, propylcobalamin, butylcobalamin, pentylcobalamin and hexylcobalamin [ 37 ]. MMACHC catalyzed the removal of the alkyl group at the upper axial position of all of the MeCbl analogs, however, the rate of dealkylation decreased with increasing alkyl chain length [ 38 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 98%
“…The authors reported that cblC bound both MeCbl and AdoCbl inducing their base-off conformation [ 36 ]; however, it did not catalyze the dealkylation of MeCbl and AdoCbl, the two major dietary forms of Cbl. This intriguing finding was re-examined via ex vivo studies [ 37 ], and a new function was uncovered for the cblC protein: MMACHC is also a Cbl dealkylase [ 37 ]. Mechanistically, dealkylation of AdoCbl and MeCbl is distinct from the decyanation pathway.…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
See 1 more Smart Citation
“…This is not entirely a "black box." Through the use of the painstaking approaches of fibroblast complementation experiments 7 and their companion cell culture studies, 8 much information has accrued from classic bedside-to-bench study of patients with puzzling disorders affecting Cbl-dependent pathways. For example, in a recent study, MMACHC, a versatile cytosolic Cbl trafficking agent that is impaired in the cblC group of inborn errors of Cbl metabolism, has been shown to catalyze the conversion of alkylcobalamins using the thiolate of glutathione to generate reduced cobalamin and the corresponding glutathione thioether.…”
Section: Ins and Outs Of Cellular Cobalamin Transport ---------------mentioning
confidence: 99%
“…4,6 Although ADAMTS13 testing is not required for initial diagnosis and decision-making for plasma therapy, it may help confirm clinical diagnosis and predict long-term outcomes. 4,7,8 Plasma ADAMTS13 activity less than 5% and/or identification of autoantibodies against ADAMTS13 is considered to be highly specific for TTP, 9 if a disseminated intravascular coagulation (DIC) is not present. In patients with DIC, acquired severe deficiency of plasma ADAMTS13 was observed.…”
mentioning
confidence: 99%